Noise induced hearing loss-a review of literature - V. Kadavil, Shahinas; Nasif, Mohammed; Sirajudeen, Jaseem (International Journal of Research in Medical Sciences, 2025)
Noise-induced hearing loss (NIHL) is one of the most prevalent occupational and environmental health concerns worldwide. First identified as "boilermaker’s disease," NIHL remains the second most common cause of hearing impairment after presbycusis, affecting millions globally. This article explores the pathophysiology of NIHL, including harmful noise levels, cochlear damage mechanisms, oxidative stress, and genetic predispositions. It also reviews current diagnostic approaches, such as pure-tone audiometry, otoacoustic emissions (OAE), and electrophysiological testing, which help in early detection. The prevention of NIHL is discussed in the context of global legislative efforts, hearing conservation programs, and protective devices. Additionally, pharmacological advancements, including antioxidants, anti-inflammatory agents, and emerging gene therapies, are highlighted as potential interventions. With increasing noise pollution from occupational and recreational sources, understanding NIHL and its management is critical for reducing its long-term impact on public health.